Pendampingan dalam Pencapaian Sustainable Development Goals Di Desa Petapahan Jaya Kecamatan Tapung Kabupaten Kampar - Rury Febrina; Muhammad Aulia; Andre Azhari; Wadiah Amalina; Sulistiawati Sulistiawati; Atika Indriani; Reni Ramadhani; Endang Rahayu; Tika Eriyanti; Rezaldi Utama; Ahmad Zailani (Asosiasi Dosen Akuntansi Indonesia, 2022)
The Service Program is an activity in providing knowledge and experience possessed by lecturers and students to the community. The problems experienced by Petapahan Jaya Village are related to data accuracy, the SDGs points of the Village have not been implemented optimally, including those related to tourism and Micro, Small and Medium Enterprises (MSMEs). The lack of innovation to make tourism objects attractive causes agro-tourism to no longer operate, and the limited knowledge possessed by MSME owners in using technology, and access to the outside world so that business owners sell only to meet family needs and not serve as opportunities to explore the world. wider. The implementation method includes data and information collection, drafting work programs, field surveys, mentoring and making MSME promotional videos. The result is the implementation of SDGs data collection activities, assistance to develop the potentials, especially in the field of agro-tourism and MSMEs. It is hoped that the knowledge gained can be applied in the MSME business so that it can improve the economy of the people of Petapahan Jaya Village